The systematics of Boulengerula fischeri (Amphibia: Gymnophiona: Caeciliidae) based on morphological and molecular data - Gower, David J.; Papadopoulou, Anna; Doherty-Bone, Thomas M.; Pupin, Fabio; San Mauro, Diego; Loader, Simon P.; Wilkinson, Mark (Zootaxa, 2011)
Eight new specimens are reported for the caecilian amphibian Boulengerula fischeri, a species known in detail previously only from its holotype collected in 1987. The new material was collected at the type locality in Rwanda in 2009, and is used to expand and refine the morphological characterization of the species. Mitochondrial and nuclear gene sequences were used to assess the phylogenetic position of B. fischeri in the context of a recent molecular phylogeny of six of the seven other species of Boulengerula (from Kenya and Tanzania). Among nominal species, only B. denhardti remains to be included in molecular phylogenetic studies of Boulengerula. Boulengerula is recovered as monophyletic, with either B. fischeri or (more probably) B. boulengeri sister to all other sampled species. There are at least three deep lineages within Boulengerula: (1) B. boulengeri, (2) B. fischeri, and (3) all other Eastern Arc Mountain and Coastal Forest species from Kenya and Tanzania. The status of Afrocaecilia, a genus erected by Taylor in 1968 to contain all Boulengerula except B. boulengeri, is not yet resolved.